Optical Transmission: Enhanced Optical Transmission through MacEtch‐Fabricated Buried Metal Gratings (Adv. Mater. 7/2016). Issue 7 (11th February 2016) - Liu, Runyu; Zhao, Xiang; Roberts, Christopher; Yu, Lan; Mohseni, Parsian K.; Li, Xiuling; Podolskiy, Viktor; Wasserman, Daniel
Abstract : On page 1441, D. Wasserman and co‐workers demonstrate a nanostructured thin film formed by engraving a thin, patterned metal layer into a semiconductor substrate via the MacEtch technique. The patterned film allows for enhanced electrical contact and simultaneously transmits more light than a smooth air‐semiconductor interface. The demonstrated approach has the potential for integration with a wide range of optoelectronic devices.